Analytical Performance of Multiplex Real-Time PCR for Six Sexually Transmitted Pathogens - Kim, Yoonjung; Kim, Juwon; Lee, Kyung-A (Clinical laboratory (Heidelberg), 2015)
Most organisms that cause sexual transmitted diseases (STDs) are fastidious pathogens that are difficult to detect with conventional microbiological methods and the proportions of multiple infections were noted up to 39.3% among the STI-positive subjects. However, only a few multiplex PCR and multiplex real-time PCR tests that can screen more than six microorganisms that cause STDs have been assessed. A total of 114 endocervical swabs (ThinPrep PAPTEST PreservCyt Solution, Hologic Inc., Marlborough, MA, USA) were collected from healthy Korean women. Chlamydia trachomatis (CT), Neisseria gonorrhoeae (NG), Mycoplasma genitalium (MG), Mycoplasma hominis (MH), Ureaplasma urealyticum (UU), and Trichomonas vaginalis (TV) were detected by uniplex PCR with Seeplex kits and by multiplex real-time PCR with Real-Q Kits (Biosewoom Inc., Seoul, Korea). To evaluate analytical sensitivity, plasmids containing target genes from CT, NG, MG, MH, UU, and TV were serially diluted five times with saline buffer and replicated eight times per dilution. Real-Q STIs Kit assays showed 100% sensitivity for detecting MH, MG, CT, TV, NG and 94.1% sensitivity for detecting UU. In addition, it showed 100% specificity for UU, MH, MG, CT, TV, and NG. The analytic sensitivity of UU (95% probit = 17.3 copy/μL, 95% CI = 11.6 to 138.6) and MH (95% probit = 30.9 copy/μL, 95% CI = 20.6 to 169.9) was relatively lower than for others pathogens. Thus, the cutoff Ct value of < 45 for UU and MH and a cutoff Ct value of < 38 for CT, MH, NG, TV could minimize differences in detection limit among the six STIs (95% probit values = 5.3 to 14.6) and to optimize overall diagnostic performance. For medical applications of a multiplex real-time PCR assay, one kind of cutoff value, which is according to manufacturer's instructions, was generally used without the consideration of lowest actual detectable concentration of each target substance. However, analytical performance at the low concentration limit often defines the ability of the test to diagnose disease and determine treatment endpoints. Therefore, suitable cutoffs for negative or positive screens by multiplex real-time PCR should be evaluated for accurate diagnosis.